Candida lusitaniae – a case report of an intraperitoneal infection - Wawrysiuk, Sara; Rechberger, Tomasz; Futyma, Konrad; Miotła, Paweł (Menopause Review/Przegląd Menopauzalny, 2018)
Candida lusitaniae is a rare opportunistic yeast which is known for its resistance to amphotericin B (AmB). It is responsible for about 19.3% of all infections caused by non-Candida albicans species, and for about 1.7% of all cases of genitourinary candidiasis brought about by the entire spectrum of Candida species. Most commonly it occurs in patients with hematologic malignancies, especially when a patient is receiving chemotherapy. Candida lusitaniae infection usually presents with fungemia; however, only 7.3% of all patients will develop peritonitis. This case study describes an immunocompetent female patient with an intraperitoneal infection caused by C. lusitaniae after laparoscopic hydrosalpinx surgery. The patient was treated with fluconazole according to susceptibility testing. Fluconazole was implemented both orally and by transvaginal injection into the space after the evacuated pseudocyst. Conservative treatment resulted in a temporary improvement of the patient’s condition and a reduction of the pseudocyst. Candida lusitaniae is very similar to other Candida species in generating systemic and local infections – mainly in compromised patients. It is also unique in its ability to develop resistance to AmB. Proper identification and quick implementation of selective therapy with the right anti-fungal drug are crucial for successfully treating infected patients. Surgery should always be considered as a final treatment option.